Recycled polyethylene (RPE) modified asphalt mixtures: Performance predictions using pavement Mechanistic-Empirical design and evaluation of return on investment. (21st November 2022) - Abdalfattah, Ibrahim A.; Mogawer, Walaa S.; Stuart, Kevin
Highlights: AASHTOWare PMED was utilized for predicting the rutting and fatigue cracking of RPE modified asphalt mixtures. RPE mixtures prepared using both the dry and wet processes showed better predicted performances than the control mixture. Using RPE by the asphalt industry could provide a higher ROI and a sustainable pavement. The dry process was more cost-effective than the wet process as indicated by lower NPVs. Abstract: The objectives of this study were to evaluate the impact of using recycled polyethylene (RPE) on the predicted rutting and bottom-up fatigue cracking of RPE modified asphalt pavement sections and on the return on investment (ROI). The AASHTOWare Pavement Mechanistic-Empirical Design (PMED) was used to predict rutting and bottom-up fatigue cracking. Life-cycle cost analyses using FHWA RealCost were used to analyze the return on investment (ROI). Three Superpave 12.5-mm mixtures were evaluated: one control and two RPE modified mixtures designed using wet and dry processes. To increase the prediction accuracies, local laboratory-derived calibration coefficients were used in AASHTOWare PMED based on the repeated load permanent deformation test (RLPDT) and flexural bending beam fatigue tests. Using time versus asphalt concrete rutting and bottom-up fatigue cracking charts, the service life for initial construction and subsequent future pavement rehabilitation/preservation activities were determined for each pavement section. The ROI was then evaluated using a 30-year analysis period. The most cost-effective pavement over the 30-year analysis period was provided by the pavement section produced using the dry process followed by the wet process while the least cost-effective pavement was the control pavement section. Hence, the study presented in this paper beneficially contributed to the current state-of-the-practice by presenting how recycled plastics impact predicted rutting and bottom-up fatigue cracking performances and the return on investment (ROI) when using both wet and dry mixing processes.